Salted Fish Processing Business Analysis In Panipahan District of Pasir Limau Kapas Rokan Hilir Riau Province - Fitratul Fajri; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in October 2014 held at Panipahan District ofPasir Limau Kapas Rokan Hilir Riau Province, the method used in this study is asurvey method. The data collected is secondary data. Respondents in this study is thesalted fish processing business operators in Bangliau in Panipahan. Intake ofinformants is done by purposive sampling that intentionally with predeterminedcriteria, then the respondent is to support and strengthen the secondary data drawnfrom relevant agenciesThis study aims to determine the total investment, income and feasibility ofsalted fish processing business in Big Bangliau, Bangliau Medium and SmallBangliau in Panipahan District of Pasir Limau Kapas Rokan Hilir Riau Province.Based on the results, the average anchovies are processed in each of his Bangliauevery month that the Big Bangliau 5000 kg, 2300 kg Bangliau Medium and SmallBangliau 550 kg. The total investment in each Bangliau is Big BangliauRp.263.052.500, Medium Bangliau Rp.157.057.500 and Small BangliauRp.47.430.500. Net income each Bangliau is Bangliau Big Rp.55.425.000, BangliauMedium USD 20.282.5000 and Small Bangliau Rp.3.469.500 per month. RevenueAnalysis based on various criteria, RCR and PPC can be said of salted fishprocessing business worth developing.Keyword: Income Analysis, RCR, PPC